2013
DOI: 10.1111/dom.12239
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin compared with other oral anti‐diabetes treatments when added to metformin monotherapy: a systematic review and network meta‐analysis

Abstract: Compared with DPP-4 inhibitors, TZDs and sulphonylureas, dapagliflozin offers similar HbA1c control after 1 year, with similar or reduced risk of hypoglycaemia and the additional benefit of weight loss, when added to metformin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
2
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 51 publications
5
54
2
9
Order By: Relevance
“…Consistent with previous findings from other laboratories (15,16,17,18), we demonstrated that sitagliptin lowered the HbA1c, FPG concentration, 2hPG, FAT (%), FFA, serum TG, and HOMA-IR in nT2DM patients. As expected, treatment with sitagliptin led to a small decrease from baseline in body weight, with no significant difference compared with the placebo group.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous findings from other laboratories (15,16,17,18), we demonstrated that sitagliptin lowered the HbA1c, FPG concentration, 2hPG, FAT (%), FFA, serum TG, and HOMA-IR in nT2DM patients. As expected, treatment with sitagliptin led to a small decrease from baseline in body weight, with no significant difference compared with the placebo group.…”
Section: Discussionsupporting
confidence: 93%
“…Per il trattamento con insulina in monoterapia o insulina combinata con gli altri antidiabetici orali è stata stimata un'incidenza annuale di eventi ipoglicemici severi pari a 2,44% nel caso di insulina basale e a 5,04% per l'insulina basal-bolus (17,18). Per i trattamenti con gli altri antidiabetici orali senza associazione a insulina, sulfaniluree o repaglinide, è stata assunta un'incidenza annuale di eventi ipoglicemici severi pari a zero (18)(19)(20). Il costo unitario per la gestione di un evento ipoglicemico severo è stato considerato pari a €1.911,18 sulla base di uno studio osservazionale italiano in cui sono stati analizzati 3516 eventi di ipoglicemia grave, di cui il 33,1% aveva richiesto ospedalizzazione (21).…”
Section: Dati Dell'analisiunclassified
“…In addition to obvious defects in neuromuscular junction (NMJ) maturation, decreased SMN results in early abnormalities in synaptic input from muscle fibers to motor neurons within the spinal cord (2,3). Both SMA mouse models and severely affected human infants exhibit abnormalities in myofiber maturation, muscle size, and muscle function (4)(5)(6). Furthermore, there is evidence that SMN-intrinsic defects in Schwann cells promote SMA pathogenesis, and peripheral nerve myelination is abnormal in severely affected infants (7).…”
Section: Smn-targeted Therapeutics: the Hope And The Hypementioning
confidence: 99%